PALLIATIVE CARE IN PRIMARY HEALTH CARE - Scremin, Marlete; Carl Silva, Jean; Gonçalves Rocha, Amanda; Luisa de Morais Prates, Maria; Medawar Leão, Harley; Danielle Carvalho Silva, Jheniffer; Alencar Fróes, Karine; Dourado Souza, Fabiana; Gonçalves de Amorim, Aline; Anelita Pereira Souza, Lunny; Teixeira de Freitas, Getúlio; Rodrigues Cordeiro, Iolanda; et al. (Health and Society, 2026)
This study sought to understand the profile of productions on palliative care in primary health care. An integrative literature review was conducted, and articles retrieved from the secondary databases Virtual Health Library, Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online and Online System for Searching and Analyzing Medical Literature were analyzed using the descriptors palliative care, primary health care and basic care. The palliative care movement has been growing and gaining notoriety due to the demographic and epidemiological transition, characterized by the increase in the adult and elderly population and, consequently, by changes in clinical processes, leading to a gradual increase in chronic and complex diseases that affect multiple organs, which sometimes threaten the continuity of life. The studies highlight the need for training professionals, the development of specific protocols and the implementation of strategies that promote more humanized, continuous and person-centered care.